2016
DOI: 10.5005/jp-journals-10002-1192
|View full text |Cite
|
Sign up to set email alerts
|

Next-day Parathyroid Hormone as a Predictor of Post-thyroidectomy Hypocalcemia

Abstract: Aims Total thyroidectomy is significantly complicated by parathyroid dysfunction and hypocalcemia. These aspects impact the decision regarding the timing of discharge and quantum of calcium supplementation required. Therefore, we aimed at evaluating the accuracy of next-day parathyroid hormone (PTH) level as a predictor of post-thyroidectomy hypocalcemia. Secondly, we aimed at establishing our institution's postoperative PTH level, which can accurately predict the development of post-thyroidectomy hypocalcemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Other published studies have proposed cutoffs between 6 and 15 pg/mL but these studies differed in study design, population studied, the definition of hypocalcemia, the technique of PTH measurement, the protocol of calcium/calcitriol supplementation of calcium/calcitriol, and possibly some undetermined factors. 2,11,13,18,25,26 A prospective study having a patient population and methodology similar to ours reported a cutoff of PTH measured on the morning of the first postoperative day to be 6 pg/mL. 18 The definition of hypocalcemia used in this study was a serum albumin-corrected calcium <8.0 mg/dL, and no differentiation was made between patients having biochemical or clinical hypocalcemia.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Other published studies have proposed cutoffs between 6 and 15 pg/mL but these studies differed in study design, population studied, the definition of hypocalcemia, the technique of PTH measurement, the protocol of calcium/calcitriol supplementation of calcium/calcitriol, and possibly some undetermined factors. 2,11,13,18,25,26 A prospective study having a patient population and methodology similar to ours reported a cutoff of PTH measured on the morning of the first postoperative day to be 6 pg/mL. 18 The definition of hypocalcemia used in this study was a serum albumin-corrected calcium <8.0 mg/dL, and no differentiation was made between patients having biochemical or clinical hypocalcemia.…”
Section: Discussionmentioning
confidence: 71%
“…2,11,13,18,25,26 A prospective study having a patient population and methodology similar to ours reported a cutoff of PTH measured on the morning of the first postoperative day to be 6 pg/mL. 18 The definition of hypocalcemia used in this study was a serum albumin-corrected calcium <8.0 mg/dL, and no differentiation was made between patients having biochemical or clinical hypocalcemia. Additionally, the protocol of calcium/calcitriol supplementation was not specified.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation